Attaining ISO 15189 accreditation through SLMTA: A journey by Kenya's National HIV Reference Laboratory - Thomas Gachuki; Risper Sewe; Jane Mwangi; David Turgeon; Mary Garcia; Elizabeth T. Luman; Mamo Umuro (AOSIS, 2014)
Background: The National HIV Reference Laboratory (NHRL) serves as Kenya's referral HIV laboratory, offering specialised testing and external quality assessment, as well as operating the national HIV serology proficiency scheme. In 2010, the Kenya Ministry of Health established a goal for NHRL to achieve international accreditation. Objectives: This study chronicles the journey that NHRL took in pursuit of accreditation, along with the challenges and lessons learned. Methods: NHRL participated in the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme from 2010-2011. Improvement projects were undertaken to address gaps in the 12 quality system essentials through development of work plans, team formation, training and mentorship of personnel. Audits were conducted and the scores used to track progress along a five-star grading scale. Standard quality indicators (turn-around time, specimen rejection rates and service interruptions) were measured. Costs of improvement projects and accreditation were estimated based on expenditures. Results: NHRL scored 45% (zero stars) at baseline in March 2010 and 95% (five stars) after programme completion in October 2011; in 2013 it became the first public health laboratory in Kenya to attain ISO 15189 accreditation. From 2010-2013, turn-around times decreased by 50% - 95%, specimen rejections decreased by 93% and service interruptions dropped from 15 to zero days. Laboratory expenditures associated with achieving accreditation were approximately US $36 500. Conclusion: International accreditation is achievable through SLMTA, even for a laboratory with limited initial quality management systems. Key success factors were dedication to a shared goal, leadership commitment, team formation and effective mentorship. Countries wishing to achieve accreditation must ensure adequate funding and support.